Device identifier for pre-screening of depression assessment - Muhammad Soffian Wong, Nor Athirah; Toha, Siti Fauziah; Nik Hashim, Nik Nur Wahidah; Abu Hanifah, Rabiatuladawiah (Kansai University Japan., 2020)
Current depression pre-screening session is usually completed with a tool such as the Depression, Anxiety, and Stress Scale (DASS21) before proceeding with treatment. Development of a device for depression measurement is hoped to overcome the issues related to time management and paper waste during assessment process. The device may also be useful as an assistance to other assessment method in delivering the final diagnosis. Data input and output of DASS21 has been utilized for the system identification technique where analysis comparison was conducted using ARX and transfer function model. The result shows that the transfer function model of order 2 outperform ARX with best fit of 98.1%. A device identifier was developed in order to assess the level of depression by implementing the transfer function into the Arduino code to predict the result from the user input.